Immunoserologic Pepsin Detection in The Saliva as a Non-Invasive Rapid Diagnostic Test for Laryngopharyngeal Reflux - Emre Ocak; Gözde Kubat; İrfan Yorulmaz (Balkan Medical Journal, 2015)
Background: The most common tool for the diagnosis of laryngopharyngeal reflux (LPR) is still 24-hours esophageal pH monitoring; there is lack of non-invasive, less expensive and accurate diagnostic tools for this frequent disease.